efektivitas EFEKTIVITAS MOBILE LEARNING BLOOKET TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VIII DI SMPN 4 BISSAPPU KABUPATEN BANTAENG - Rahmat Kurnia; Kasman; wahyuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Rahmat Kurnia, 2025. The Effectiveness of Mobile Learning Blooket on Indonesian Language Learning Outcomes of Class VIII Students at SMPN 4 Bissappu, Bantaeng Regency. Thesis, Educational Technology Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Mr. Kasman and Supervisor II Mr. Wahyuddin. This study aims to determine the effectiveness of mobile learning blooket on Indonesian language subjects in class VIII of SMPN 4 Bissappu. This type of research is quantitative or experimental research (true experimental) using Pretest-Posttest Control Group Design, The population in this study were all students of SMPN 4 Bissappu consisting of 3 classes, a total of 78 people. The sample in this study were two classes from 3 existing population classes. One class as an experiment and one class as a control class. The two classes are: classes VII and VIII, where VIII is the experimental class and class VII is the control class, selected through Purposive Sampling. Data collection techniques in this study are observation, testing, and documentation. The results of this study indicate that mobile learning blooket in Indonesian language subjects is effectively used in class VIII of SMPN 4 Bisappu. The calculation results show a value of t count = 10,037 and a value of t table = 1,720. based on the testing criteria if t count ≥ t table then HO is rejected and Hi is accepted. With the calculation results t count ≥ t table or 10. 037 ≥ 1,720 thus Ho is rejected and Hi is accepted. This proves that the use of mobile learning blooket in class VIII of SMPN 4 Bisappu is effective in the learning process. Compared to using conventional learning models.